Benign tumors in gynecology and obstetrics. Benign ovarian tumors, diagnosis, clinical and management in pregnancy. - Fernández Molinari, Luis (2015)
Ovarian tumors are relatively common during pregnancy. Eastman and Hellman reported an incidence of ovarian cysts during pregnancy of 1 in 81 and Grimes et al. They show that one in 328 pregnancies have a big enough risk to mean cyst.